A Mathematical Model for the Saturation Effects of Radiotherapy with Oscillating Tumor Density - Vithanage, G.V.R.K.; Wattetenne, A.R.M. Hasini Parami; Jayakody, K.A. Nirupadhi Divyanjali; Dhanushika, M. Sawani; Dassanayaka, Sachith (Journal of Advances in Applied & Computational Mathematics, 2025)
In the present-day society, cancer has become a challenge that threatens millions of human lives and causes many deaths. Throughout this research, we have developed a mathematical model to describe the radiotherapy treatment. There is a competition between tumor cells and normal cells; we use Lotka-Volterra dynamics to represent that biological idea in a mathematical model. In radiotherapy, ionizing particles attack the DNA of both tumor cells and normal cells. This process occurs in a medium with oxygenated tissues, and it has a saturation level. Previous researchers have not considered the saturation effects of radiotherapy in their models; however, our model incorporates the Michaelis-Menten term to represent these effects, which is the main novelty in this research with respect to previous works. We assume that other reactions are occurring according to the Mass Action Law, and also that radiotherapy targets both tumor cells and normal cells with the same intensity. First, we conduct a stability analysis of the system and then simulate the system by using time series analysis. We observed that in most cases, a stable equilibrium point can occur or periodic behavior may emerge in the population levels. By conducting a local sensitivity analysis, we identified the most sensitive parameters important in clinical treatments. We then conduct a bifurcation analysis for the most sensitive parameters, observing critical values for these parameters that must be maintained within a specific range to achieve an optimal treatment outcome. Primarily, we investigated the optimal range for the killing rate of tumor cells and discussed how the half-saturation constant effects therapy. These results will be crucial for achieving better clinical outcomes in radiotherapy.